2002
DOI: 10.4049/jimmunol.168.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Development and Homeostasis of T Cell Memory in Rhesus Macaque

Abstract: The rhesus macaque (RM) is a critical animal model for studies of viral pathogenesis and immunity, yet fundamental aspects of their cellular immune response remain poorly defined. One such deficiency is the lack of validated phenotypic signatures for their naive and memory T cell subsets, and the resultant unavailability of accurate information on their memory T cell development, homeostasis, and function. In this study, we report a phenotypic paradigm allowing definitive characterization of these subsets and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

37
465
2
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 438 publications
(505 citation statements)
references
References 59 publications
37
465
2
1
Order By: Relevance
“…Memory cell differentiation was performed using CD28 and CD95 phenotypic markers as described elsewhere [29]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Memory cell differentiation was performed using CD28 and CD95 phenotypic markers as described elsewhere [29]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cells were then treated with fixation/permeabilization solution (BD Biosciences) at 2Â concentration for 10 min in the dark at room temperature as described earlier [29,48]. Following two washes with dPBS/BSA, mAb anti-CD69-allophycocyanin-Cy7 (clone FN50)/anti-IFN-c-FITC (clone 4S.B3)/anti-TNF-a-FITC (clone Mab11) or anti-MIP-1b-PE (clone D21-1351) were added at room temperature for 30 min.…”
Section: Cytokine Flow Cytometry Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…CD4 and CD8 T cells can be subdivided into three major subsets using antibodies directed against surface markers CD28 and CD95: (1) naïve T cells (Na, CD28+CD95−), (2) central memory T cells (CM, CD28+CD95+), and (3) effector memory T cells (EM, CD28−CD95+) as illustrated in Fig. 1a (Jankovic et al 2003;Pitcher et al 2002). We have previously shown that, as described for humans (Pawelec et al 2009), increasing age results in a decreased frequency of naïve T cells and an accumulation of memory cells, especially EM T cells in rhesus macaques (Jankovic et al 2003).…”
Section: Impact Of Ovariectomy On the Frequency Of Naïve T Cellsmentioning
confidence: 99%